Microbial Electrochemically Assisted Treatment Wetlands: Current Flow Density as a Performance Indicator in Real-Scale Systems in Mediterranean and Northern European Locations - Peñacoba-Antona, Lorena; Ramirez-Vargas, Carlos Andres; Wardman, Colin; Carmona-Martinez, Alessandro A.; Esteve-Núñez, Abraham; Paredes, Diego; Brix, Hans; Arias, Carlos Alberto (Frontiers in Microbiology, 2022)
A METland is an innovative treatment wetland (TW) that relies on the stimulation of electroactive bacteria (EAB) to enhance the degradation of pollutants. METland is designed in short-circuit mode (absence of external circuit) by means of an electro-conductive bed capable of accepting electrons from microbial metabolism of pollutants. Although METland are proved to be highly efficient for removing organic pollutants, the study of in situ EAB activity in full scale systems is a challenge due to the absence of two-electrodes configuration. For the first time, four independent real-scale METland systems were tested in terms of removal of organic pollutants and nutrients; thus, a correlation with the electroactive response generated by the presence of EAB was established. The removal efficiency of the systems was enhanced by plants and mixed oxic-anoxic conditions, with an average removal of 56g COD mbed material-3 d-1 and 2g TN mbed material-3 d-1 for Ørby 2 (partially saturated system). Estimated electron current densities (J) provide evidence of the presence of EAB and its relationship with the removal of organic matter. The tested METland systems reached max. values of 188.14 mA m-2 (planted system; IMDEA 1), 223.84 mA m-2 (non-planted system; IMDEA 2), 125.96 mA m-2 (full saturated system; Ørby 1), and 123.01 mA m-2 (partially saturated system; Ørby 2); such electron flow values were remarkable for systems that were not designed for energy harvesting and unequivocally show how electrons circulate even in absence of two electrode systems. The relation between organic load rate at inlet (OLR) and colulombic effciency (CE; %) showed a decreasing trend, with values ranging between 8.8-53% (OLR from 2.0 to 16.4 g COD m-2 d-1) for IMDEA systems, and between 0.8-2.5 % (OLR from 41.9 to 45.6 g COD m-2 d-1) for Ørby systems. This pattern denotes that the treatment of complex mixtures such as real wastewater with high and variable OLR should not necessarily imply the result of high CE values. METland technology was validated as an innovative an efficient solution for treating wastewater from decentralized locations.